Adaptasi Alat Ukur Stres Berkendara bagi Pengendara Motor di Indonesia - Novika Grasiaswaty; Alexandra Aliviary; Nuri Sadida (Universitas Muhammadiyah Lampung, 2021)
ABTRACTThe driving stress scale is one of the tools for measuring stress on car drivers and so far, the Indonesian version has not been found. Adaptation of this measuring tool is needed considering that the construct has been more suitable for car drivers, while for motorbike riders, adaptation is needed, especially in Indonesia. The adaptation of measuring instruments using driving stress consists of 16 items and is a unidimensional measuring instrument. The adaptation process follows six stages (translate-synthesis-backward translate), both qualitative and quantitative. The results of the measurement tool translation were then given to eight online motorcycle taxi drivers and they were asked to read each item to check understanding in each item. Based on the qualitative process, some words were changed. The DS-Indonesia version was then returned to three online motorcycle taxi drivers to be re-tested for readability. These results were then tested (try out) to 28 online motorcycle taxi drivers to be analyzed quantitatively. Improvements were made again so that there were some item changes. The final result of this item was then collected data on 200 online motorcycle taxi drivers. Reliability testing and Confirmatory Factor Analysis with the R platform and Lavaan packages were used to check the suitability of each item with the DS-Indonesia unidimensional factor. It is known if the value of x2 : 57.114 p<0.001, CFI = 0.969; TLI = 0.906 . RMSEA =0.078 ; SRMR = 0.040 which indicates that the results of the DS-Indonesia adaptation data have a fairly good fitness value. The inter-item results are in the good range and the correlation with BFI-Indonesia shows that DS-Indonesia correlates with the neuroticism, consiousness, agreeableness and openness traits but not with extraversion.ABSTRAKDriving stress scale merupakan salah satu alat ukur stres pada pengendara mobil dan sejauh ini, belum ditemukan alat ukur versi bahasa Indonesia. Adaptasi alat ukur ini diperlukan mengingat konstruk tersebut selama ini lebih cocok untuk pengendara mobil, sementara untuk pengendara motor diperlukan adaptasi lagi terutama di Indonesian. Pengadaptasian alat ukur menggunakan driving stress terdiri dari 16 aitem dan merupakan alat ukur unidimensional. Proses adaptasi mengikuti enam tahapan (translate-sintesa-backward translate), baik kualitatif maupun kuantitatif. Hasil terjemahan alat ukur tersebut kemudian diberikan kepada delapan orang pengendara ojek online dan mereka diminta untuk membaca setiap aitem untuk mengecek pemahaman dalam setiap aitem. Berdasarkan proses kualitiatif tersebut, beberapa kata diubah. Versi DS-Indonesia ini kemudian dikembalikan kepada tiga orang pengemudi ojek online untuk kembali diuji keterbacaan. Hasil ini kemudian dilakukan uji coba (try out) kepada 28 orang pengemudi ojek online untuk dianalisis secara kuantitatif. Perbaikan kembali dilakukan sehingga terdapat beberapa perubahan aitem. Hasil akhir aitem ini kemudian dilakukan pengambilan data kepada 200 orang pengemudi ojek online. Uji reliabilitas dan Confirmatory Factor Analysis dengan platform R dan Lavaan packages digunakan untuk mengecek kesesuian setiap aitem dengan faktor unidimensional DS-Indonesia. Diketahui jika nilai x2 : 57.114 p<0.001, CFI = 0.969; TLI = 0.906 . RMSEA =0.078 ; SRMR =0.040 yang mengindikasikan jika hasil data adaptasi DS-Indonesia memiliki nilai fitness yang cukup baik. Hasil inter-aitem berada pada rentang baik dan korelasi dengan BFI-Indonesia mneunjukkan jika DS-Indonesia berkorelasi dengan trait neuroticism, consiousness, agreeableness dan openness tetapi tidak dengan extraversion.